Strategi Loyalitas Kerja pada Azalea Gorden - Sari, Eka Permata; Prayudi, Feri Yoga; Sandi, Santi Pertiwi Hari; Hidayaty, Dwi Epty (SAFE-Network, 2024)
Azalea Gorden is a Micro, Small and Medium Enterprise (MSME) engaged in the production and sale of curtains with the best quality and competitive prices since 2005. This study aims to determine employee work loyalty at Azalea Gorden. The focus of this study is to understand employee work loyalty strategies and their impact on employee productivity. The method used is descriptive and Observative, by describing the situation through observations that occur in the field. The data obtained are the results of interviews with the Owner / Shop Owner of Azalea Gorden. The results of the study indicate that there are several factors that influence employee work loyalty at Azalea Gorden. These factors include job satisfaction and a positive work climate, and it was also found that high work loyalty can have a positive impact on employee productivity. The implication of this study is the importance of MSMEs in creating a work environment that motivates and supports employees to remain loyal. In managing employees, companies must pay attention to job satisfaction and a positive work climate.